2011
DOI: 10.1177/0020764011430038
|View full text |Cite
|
Sign up to set email alerts
|

Suicide rates in the national and expatriate population in Dubai, United Arab Emirates

Abstract: Further research on risk factors for and protective factors against suicide, particularly among the expatriate population, is needed. Epidemiological monitoring of suicide trends at the national level and improvement of UAE suicide statistics would provide useful information for developing suicide prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
3
26
2
Order By: Relevance
“…Another possible reason for higher suicide cases in rural region could be to the dearth of immediate medical interventions or specialized medical staff required to deal with self harm or suicide attempt case (Patel et al, 2012). The present study observation of higher suicide rate among male than compared female is in agreement with other epidemiological studies (Badiye et al, 2014;Chettri et al, 2016;Dervic et al, 2012) reporting 2-3 times higher suicide deaths among males than compared to female counterpart. The gender difference in suicide mortality could be attributed to the difference in preference of more lethal and violent suicide method (Mergl et al, 2015), alcohol abuse and its intoxication at the time of suicide attempt (Menon et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Another possible reason for higher suicide cases in rural region could be to the dearth of immediate medical interventions or specialized medical staff required to deal with self harm or suicide attempt case (Patel et al, 2012). The present study observation of higher suicide rate among male than compared female is in agreement with other epidemiological studies (Badiye et al, 2014;Chettri et al, 2016;Dervic et al, 2012) reporting 2-3 times higher suicide deaths among males than compared to female counterpart. The gender difference in suicide mortality could be attributed to the difference in preference of more lethal and violent suicide method (Mergl et al, 2015), alcohol abuse and its intoxication at the time of suicide attempt (Menon et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…A recent systematic review of all studies related to migrant mental health in the Persian Gulf identified fewer than a dozen articles published between 2002 and 2010 [22]. These limited studies offer quantitative evidence of a high rate of suicide [23][24][25][26] and psychiatric symptoms [27,28]. A small number of studies have used depression scales to quantify burdens and covariates of mental illness among migrants [29,30].…”
Section: Plos Medicinementioning
confidence: 99%
“…Globalization has increased international mobility, and in Dubai, one of the emirates in the United Arab Emirates (UAE), more than 80% of the population is foreign‐born (Dervic et al, ). The number of Koreans in the UAE has increased fourfold during the last five years, with more than 5,000 Koreans living in Dubai and around 10,000 across the UAE (Leon, ).…”
Section: Health‐promoting Behaviors In the Uaementioning
confidence: 99%
“…Engaging in HPLB is likely to be challenging for persons living in a new environment (Kim, Pearce, & Choi‐Kwon, ). Difficulty adjusting to Islamic culture, its religious beliefs, and very hot weather can negatively affect migrants' physical activity and psychological health status (Kim et al); migrants' suicide rates are seven times higher than among Arab locals (Dervic et al, ). Increases in the prevalence of hypertension and diabetes in migrants in the UAE also have been reported, possibly due to the different environment or underlying susceptibility to those conditions (Newson, ).…”
Section: Health‐promoting Behaviors In the Uaementioning
confidence: 99%